Dukungan Keluarga dalam Pencegahan Kejadian Multidrug Resistence pada Pasien Tuberculosis - Kristinawati, Beti; Rahmawati, Siti (Sekolah Tinggi Ilmu Kesehatan RS Husada, 2020)
Inadequate Tuberculosis treatment can cause drug resistance or multidrug resistant. Family support is needed in the treatment and care of Tuberculosis patients. This research aims to determine the relationship of family support with the prevention of multidrug resistance in patients Tuberculosis. The quantitative research method with a correlative descriptive design through a cross sectional approach was used in this study. Respondents involved were all tuberculosis patients in the working area of Sangkrah and Pajang Puskesmas who succeeded in the treatment and did not experience multidrug resistance as much as 48 respondents. The results of the study gained a relation between family support and the prevention of multidrug resistance with significance value p of 0.026 and emotional support is the highest form of support with an average value of 18.04.